2016
DOI: 10.1007/s00429-016-1227-8
|View full text |Cite
|
Sign up to set email alerts
|

Central relaxin-3 receptor (RXFP3) activation increases ERK phosphorylation in septal cholinergic neurons and impairs spatial working memory

Abstract: The medial septum/diagonal band (MS/DB) is a relay region connecting the hypothalamus and brainstem with the hippocampus, and both the MS/DB and dorsal/ventral hippocampus receive strong topographic GABA/peptidergic projections from the nucleus incertus of the pontine tegmentum. The neuropeptide relaxin-3, released by these neurons, is the cognate ligand for a G i/o -protein-coupled receptor, RXFP3, which is highly expressed within the MS/DB, and both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 82 publications
4
45
0
5
Order By: Relevance
“…Both H3 relaxin and 14s21 peptide significantly increased the rat food intake within the first 80 min after intranasal drug administration. This transient hyperphagia might be explained by the fact that relaxin‐3 analogues activate the MAPK/ERK signalling pathway in septal cholinergic neurons of the MS/DB (Albert‐Gasco et al, ) and support the putative mechanism by which NI relaxin‐3 projections regulate the septo‐hippocampal system (Olucha‐Bordonau et al, ). The 14s21 peptide elicited a dose‐dependent increase in ERK1/2 phosphorylation and showed the same potency as H3 relaxin.…”
Section: Discussionmentioning
confidence: 92%
“…Both H3 relaxin and 14s21 peptide significantly increased the rat food intake within the first 80 min after intranasal drug administration. This transient hyperphagia might be explained by the fact that relaxin‐3 analogues activate the MAPK/ERK signalling pathway in septal cholinergic neurons of the MS/DB (Albert‐Gasco et al, ) and support the putative mechanism by which NI relaxin‐3 projections regulate the septo‐hippocampal system (Olucha‐Bordonau et al, ). The 14s21 peptide elicited a dose‐dependent increase in ERK1/2 phosphorylation and showed the same potency as H3 relaxin.…”
Section: Discussionmentioning
confidence: 92%
“…administration of the selective RXFP3 agonist, RXFP3‐A2, increased ERK phosphorylation in septal cholinergic neurons (20 and 60 min post‐injection) and impaired spatial working memory in a spontaneous alternation test assessed 5 min post‐treatment (Albert‐Gasco et al, ). ERK1/2 activation is capable of increasing neuronal excitability through inhibition of transient potassium (A‐type) currents (Fu et al, ), but the recent study did not assess the direct or indirect nature of the excitatory/inhibitory effect of RXFP3 activation on different septal neurons, as the site of peptide administration was outside the septum (Albert‐Gasco et al, ). Moreover, these recent behavioural findings contrast with those from earlier studies, which reported an increase in the power of hippocampal θ activity following infusion of the RXFP3 agonist, R3/I5, directly into the medial septum, and an impairment in spatial memory performance in the spontaneous alternation task with intra‐septal infusion of an RXFP3 antagonist, R3(BΔ23–27)R/I5 (Ma et al, ).…”
Section: Pharmacological Effects Of Rxfp3 Activationmentioning
confidence: 99%
“…The NI/relaxin‐3 system has been shown to induce (Nunez et al, ), display coherence with (Cervera‐Ferri et al, ) and fire in a phase‐locked manner with (Ma et al, ) HC theta oscillations and modulate relevant behavioural functions such as spatial memory (Ma et al, ; Albert‐Gasco et al, ) (see Ma et al , (in press)). Interestingly, tetanic stimulation of the NI in freely‐moving rats evoked robust forward locomotion at latencies consistent with its modulation of premotor areas such as the SHS and, probably, HC theta activity (Farooq et al, ).…”
Section: Introductionmentioning
confidence: 99%